Sir Charles Grandison, Volume I-IV the Cambridge edition of the works of Samuel Richardson - Richardson, Samuel 1689-1761 (Cambridge University Press, 2022)
One of the most important novels of the eighteenth-century, Sir Charles Grandison [1753] shaped the English courtship novel, and was loved and admired by both Jane Austen and George Eliot. The book follows the life of Sir Charles, a man parallel in virtue with Richardson's female paragons Clarissa and Pamela; and a response to the fallible protagonist Tom Jones in Fielding's popular satire of moralising novels. Forming part of the first full scholarly edition of Richardson's complete works, comprehensive general and textual introductions significantly revise and advance understanding of the composition and printing history of Richardson's final novel, and reveal the central place of Sir Charles in the literature of the period. Including Richardson's Historical Index for the first time in any edition, extensive annotations and expansive notes also give readers crucial context, and provides scholars with paths to follow for future research